REGISTERS USED IN STAND-UP COMEDY “INDO” MALANG COMMUNITY - TURNIP, SURYANI DUPADES (Jurnal Ilmiah Mahasiswa FIB, 2014)
Turnip, Suryani Dupades. 2014.  Registers Used in Stand-up Comedy “Indo” Malang Community. Study Program of English, Department of Languages and Literature, Faculty of Cultural Studies, Universitas Brawijaya. Supervisor: Isti Purwaningtyas; Co-supervisor: Ida Puji Lestari. Keywords: Sociolinguistics, Register, Register Variables, Stand-up Comedy, Stand-up Comedy Indo Malang Community. Language and society are interconnected each other to create a good communication. Then, people intentionally use a specific language variety namely register to simplify the terms used. The registers can make people who do not belong to the members misinterpret the meaning because they do not know about the three kinds of register variables which construct the context of register itself; they are field, mode, and tenor. This study uses theory of Halliday and Hasan (1989) to analyze the registers which are used in stand-up comedy Indo Malang community. There are two research problems of this study: (1) What are the registers used by the members of stand-up comedy Indo Malang community? (2) How are the register variables which consist of field, mode, and tenor applied in the conversation among the members of stand-up comedy Indo Malang community? This study uses qualitative descriptive approach because the writer describes the registers used by the members of stand-up comedy Indo Malang community and how the register variables are built in the context. As the data, the writer uses the utterances which contain registers during the evaluation in JumaTawa 65. Then, the data sources of this study are the coaches and the  comics of stand-up comedy Indo Malang community. The finding shows there are 18 registers found that are used by the members during the evaluation sessions of JumaTawa 65. Then, to make the readers become more understandable about the meaning of the registers in the context, the writer defines them into common meaning and particular meaning. The writer also finds out that register variables that consist of field, mode, and tenor are important to know the topics which are discussed by the members of stand-up comedy Indo Malang community, the function of the utterances, and the relationship among the participants.  The writer suggests the next researchers to  use another way and the other theories to analyze registers phenomenon that happen in the society. They also can conduct a research in the different communities to make the language varieties become more varieties.